Unravelling the enigma of discontinuous sedimentary deposits in cold-water coral mounds in the Atlantic Ocean - Hebbeln, Dierk; Wienberg, Claudia (Frontiers in Marine Science, 2025)
Cold-water coral mounds are common along the continental margins of the Atlantic Ocean. They are formed by coral growth and sediment accumulation and consist of coral fragments embedded in hemipelagic sediments. Coral mounds are expected to provide high-resolution palaeo-records due to their elevated morphology. However, most sediment cores from coral mounds exhibit significant hiatuses (stratigraphic gaps), often spanning more than 100 kyr, raising questions about the fate of deposits formed during these periods. Three processes behind the hiatuses are critically reviewed: gravity-induced mass wasting, non-deposition, and winnowing. While mass wasting could remove entire mound layers, hydrodynamically controlled processes like non-deposition and winnowing affect fine-grained sediments and do not mobilise larger coral fragments. Evidence for large-scale mass wasting events on coral mounds remains inconclusive, suggesting that hydrodynamic processes are the primary cause of the hiatuses in the mound record. Consequently, the coral record preserved on the mounds is typically complete. Mound formation occurs during active reef growth, while during periods without reef growth, strong hydrodynamics enhanced by the mound morphology increasing turbulence around the mound prevent sustained sediment accumulation, causing the frequently observed hiatuses.